Perspecrrve, Planning and People's Participation in Proposed Social forestry Models for Economic Development and National Productivity - Shiva, Alka; Shiva, M. P. (Indian Forester, 1989)
The rate of depletion of forets for meeting various demands has been higher than the rate of replenishment of the stock, owing to the gradual increase in population and their bonafide needs. This chaotic situation can only be overcome if people's participation is energized as bas been done in Phillipines. They took such massive programmes that the people's participation took such a gigantic rate that not a single person in Phillipines was omitted who did not plant atleast 5 to 10 trees. Such steps are also necessary in India. With this contention this article highights such social forestry models which may bring economic development to the people and at the same time increase forest areas and boost the national productivity.